Treatment of pulmonary hypertension with the continuous infusion of a prostacyclin analogue, iloprost. Issue 2 (1st February 1998) - Higenbottam, T W; Butt, A Y; Dinh-Xaun, A T; Takao, M; Cremona, G; Akamine, S
Abstract : Objective: To compare prostacyclin with an analogue, iloprost, in treatment of severe pulmonary hypertension. Patients: Eight patients with severe pulmonary hypertension: primary in five, thromboembolic pulmonary hypertension in three. Methods: All patients underwent right heart catheterisation. Mean (SEM) right atrial pressure was 9.9 (2.2) mm Hg, mean pulmonary artery pressure 67.4 (3.0) mm Hg, cardiac index 1.75 (0.13) l/min/m 2 and mixed venous oxygen saturation 59.1(3.1)%. Continuous intravenous epoprostenol (prostacyclin, PGI2 ) or iloprost was given for phase I (three to six weeks); the patients were then crossed over to receive the alternate drug in an equivalent phase II. Main outcome measures: Exercise tolerance was measured at baseline and at the end of phase I and II with a 12 minute walk; distance covered, rest period, percentage drop in arterial oxygen saturation (ΔSao 2 %) and percentage rise in heart rate (ΔHR%). Results: Walking distance covered rose from (mean (SEM)) 407.5 (73) to 591 (46) m with PGI2 (p = 0.004) and to 602.5 (60) m while on iloprost (p = 0.008). Rest period decreased from 192 (73) seconds at baseline to 16 (16) seconds with PGI2 (p = 0.01) and to 58 (34) seconds with iloprost (p = 0.008). ΔHR% was 37.5(6)% at baseline, 35(3)% on PGI2, and 24(6)% on iloprost (p = 0.04). Conclusions: Both intravenous PGI2 and iloprost caused significant improvement in exercise tolerance. Iloprost offers an alternative to PGI2 treatment of severe pulmonary hypertension.